1 Corinthians 14:34-35: The Words of Paul or a Later Addition? - Bird, Victoria Anne (2023)
This study addresses the text-critical problem of 1 Corinthians 14:34-35. It examines whether the assertion that women should be silent and subordinate in the churches was an original part of Paul’s first letter to the Corinthians or a later addition. Resolving this matter is significant as 1 Corinthians 14:34-35 is the cornerstone for all debates concerning the role of women in the Christian church. The first chapter of this study addresses the external evidence. It explores the ancient manuscripts that contain 1 Corinthians 14:34-35 and early Christian and patristic writings. The latter two chapters focus on the internal evidence. They examine the likelihood of Paul writing 1 Corinthians 14:34-35 and consider the possibility of the verses being transposed or added. This study will argue that 1 Corinthians 14:34-35 was a non-Pauline addition. The verses were most likely written in the margin of a manuscript and subsequently inserted into the text of First Corinthians in two different places. It seems that Paul did not author 1 Corinthians 14:34-35 as the verses fit awkwardly in their literary context and do not reflect Paul’s typical view of women. The attitude toward women in 1 Corinthians 14:34-35 conforms with that in the pseudo-Pauline writings, and the verses closely resemble 1 Timothy 2:11-14. Therefore, it seems probable that a Christian around the beginning of the second century wrote 1 Corinthians 14:34-35 in the margin of a manuscript alongside Paul’s instructions on orderly worship (1 Cor. 14:26-40).